Approximate Controllability for Functional Equations with Riemann-Liouville Derivative by Iterative and Approximate Method. (27th June 2017) - Ibrahim, Badawi Hamza Elbadawi; Fan, Zhenbin; Li, Gang
Abstract : We discuss the functional control systems governed by differential equations with Riemann-Liouville fractional derivative in general Banach spaces in the present paper. First we derive the uniqueness and existence of mild solutions for functional differential equations by the approach of fixed point and fractional resolvent under more general settings. Then we present new sufficient conditions for approximate controllability of functional control system by means of the iterative and approximate method. Our results unify and generalize some previous works on this topic.